Knowledge Level of Farmers About Recommended Production Techniques of Bt Cotton in Punjab - Singh , Amrik; Bhalla , J. S.; Singh, Dharminder (Indian Journal of Extension Education, 2017)
Cotton is an important fibre and cash crop of India and it plays a dominant role in industrial and agricultural economy  of the country. Punjab has more than 90 per cent of total cotton area under Bt cotton. The present study was conducted in  Muktsar district of Punjab to assess the knowledge level of farmers about the recommended production techniques of Bt  cotton crop. Two villages from each of the four blocks of Muktsar district viz. Muktsar, Malout, Lambi and Kotbhai were  selected for the study and the total sample size comprised of 160 farmers for the present study. Data were collected with  the help of structured interview schedule based on Bt cotton production techniques recommended by PAU, Ludhiana. The  study revealed that a majority of the respondents (90.63%) had knowledge about recommended varieties of Bt cotton.  Only 10.00 per cent of the respondents had knowledge about the economic threshold level (ETL) of white fly, whereas  13.75 per cent of the respondents had knowledge about economic threshold level of cotton jassid. Majority of the  respondents had knowledge about the recommended insecticides for the control of jassid and bollworms. It was found that  36.88 per cent of the respondents had knowledge about the purpose of refuge crop grown in Bt cotton whereas only 8.15  per cent possessed knowledge about the ratio of Bt cotton to Non-Bt to be grown as refuge lines. Over all mean knowledge  score of the respondents was calculated to be 13.85 and majority of the respondents (60.00%) was found to have low  knowledge level about the recommended production techniques in Bt Cotton.
Keywords: Bt Cotton; knowledge; adoption; ETL; refuge lines; punjab